Evaluation of the effectiveness of vehicle roll stability control (RSC) for high center of gravity light passenger vehicles in Australasia. (18th August 2021) - Keall, Michael D.; Newstead, Stuart
Abstract: Objective: Rollover crashes, which occur when the vehicle's side or roof makes impact with the ground, present particularly serious injury risk. Higher rollover risk has been found for high riding vehicles – those with a relatively high center of gravity compared to the width of the wheel track. Electronic Stability Control (ESC), which automatically applies brakes to individual wheels and reduces engine power to help drivers regain control when traction is lost, has been shown to be effective in preventing a proportion of rollovers. A newer safety technology, Roll Stability Control (RSC), uses similar technology aimed specifically to reduce rollover risk. This study sought to estimate rollover crash rates associated with the fitment of RSC compared to non-fitment for high center of gravity (CG) light passenger vehicles using an induced exposure analysis. Methods: Police-recorded Australasian crash data were studied for the years 2008-2017. A quasi-induced exposure analysis was restricted to vehicles already equipped with ESC as vehicles fitted with RSC always have ESC fitted. Rollover risk associated with RSC fitment was assessed, controlling for year of crash, speed limit at crash location, year of vehicle manufacture, vehicle market group, driver age, driver gender and jurisdiction identifier. Results: The analysis found a statistically significant rollover risk ratio of 0.76 (95% CI 0.62-0.93), representing a 24% reduction in rollover risk, associated with RSC fitment for vehicles manufactured between 2008 and 2017. Analysis by particular market groups found significant risk ratio reductions for commercial utilities and large SUVs, but not for the other high CG market groups individually. Conclusions: These results suggest that RSC is a highly effective safety feature for high CG vehicles. Fleet data from Australia and New Zealand showed declining rates of RSC fitment over recent years for SUVs, meaning the potential road safety benefits of the technology are not being fully realized.